OWNERSHIP STRUCTURE AND CORPORATE RESTRUCTURING: DOES IT HAVE AN IMPACT? - Sri Dwi Ari Ambarwati; ST Haryono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Ownership structure has a role in decision making by the company. This study wants to examine the effect of ownership structure on the choice of corporate restructuring: asset divestment and dividend cut. This study focuses on the restructuring strategy on manufacturing firms that experience declining performance, using the proxy of decreasing Earnings Before Interest and Tax for two or more consecutive years, in the period of 2010 until 2020. Data analysis techniques using OLS Regression through Stata Program. The result shows: 1. Managerial ownership has positive impact on asset divestment, but family ownership, liquidity and inflation (as control variable) have negative impact on asset restructuring, namely, assets divestment, and 2. Family ownership have positive significant impact on financial restructuring through dividend cut, but institutional ownership have negative impact on dividend cut restructuring.. Applications/Originality/Value: This study provides strengthening empirical evidence about the impact of ownership structure on corporate restructuring (divestment and dividend cut) choices in distress firms. This study is appropriate to carried out in Indonesia, which has a high leveraged firm on average 43% and emerging market. Keyword: Managerial ownership, institutional ownership, family ownership, assets divestment, restructuring